Water Supply Quality and Health Impacts on Hill Tribe People: A Case Study of the Akha Hill Tribe Village, Chiang Rai, Thailand - Roberts, Claire; Rozek, Laura; Mingkhwan, Rachaneekorn; Kiangkoo, Nuttapohn; Janta, Peerawit; Sudsandee, Suntorn (Journal of Health Science and Alternative Medicine, 2025)
Introduction: The hill tribes in northern Thailand, including the Akha village, live in mountainous and remote areas without access to safe water from the Provincial Waterworks Authority (PWA) service. The main water supply in Akha village is mountain water, and it is without any treatment process. This study aimed to assess the quality of mountain water supply and evaluate the health risk from dermal and oral exposures in the Akha hill tribe village. Methods: Fifteen water samples were collected from water storage tanks using grab sampling techniques. The water supply quality was analyzed for turbidity, pH, total dissolved solids (TDS), hardness, total coliform bacteria (TCB), fecal coliform bacteria (FCB), cadmium (Cd), iron (Fe), mercury (Hg), and lead (Pb). All parameters were compared with PWA tap water standards. The U.S. EPA model was applied to assess health risks from the four heavy metals for adults and children in the Akha village. Results: The analysis revealed that 80% of samples exceeded the PWA standard for turbidity, 13% for pH, and 87% for Fe. TCB and FCB were detected in all mountain water samples. The hazard indices (HIs) for Cd, Fe, Hg, and Pb exposures via dermal and oral routes were below 1. Conclusion: Despite the poor water supply quality, the HIs for heavy metal exposure were below the risk threshold. Nonetheless, it is crucial for local and national policy-makers to support initiatives that provide knowledge and financial subsidies for water treatment in these remote areas to ensure safe drinking water for the hill tribe communities.